2020
DOI: 10.1016/j.jcorpfin.2020.101578
|View full text |Cite
|
Sign up to set email alerts
|

Is language an economic institution? Evidence from R&D investment

Abstract: Some languages encode future timing more ambiguously than others. We identify two economic channels through which more ambiguous reference to future timing leads to higher levels of R&D investment. Our empirical tests on country-and firm-level R&D investment confirm this prediction, even after controlling for an extensive set of formal and informal economic institutions and addressing endogeneity concern in multiple ways. Tests on patent generation provide further evidence that ambiguous reference to future ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 62 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Modality and FTR in English, Dutch and German relativity and FTR should seek to characterize cross-linguistic differences in the grammaticization of (future) predictions, which our results suggest are a more appropriate typological basis for making hypotheses about psychological discounting than the tense-centered dichotomous approaches presently predominant (K. Chen, 2013;S. Chen et al, 2017;Chi et al, 2018;Fasan et al, 2016;Figlio et al, 2016;Galor et al, 2016;Guin, 2017;Hübner & Vannoorenberghe, 2015a;Karapandza, 2016;Kim et al, 2017;Liang et al, 2018;?, ? ;Pérez & Tavits, 2017;Roberts et al, 2015;Sutter et al, 2015;Thoma & Tytus, 2018).…”
Section: P R E -P U B L I C a T I O N D R A F Tmentioning
confidence: 92%
See 1 more Smart Citation
“…Modality and FTR in English, Dutch and German relativity and FTR should seek to characterize cross-linguistic differences in the grammaticization of (future) predictions, which our results suggest are a more appropriate typological basis for making hypotheses about psychological discounting than the tense-centered dichotomous approaches presently predominant (K. Chen, 2013;S. Chen et al, 2017;Chi et al, 2018;Fasan et al, 2016;Figlio et al, 2016;Galor et al, 2016;Guin, 2017;Hübner & Vannoorenberghe, 2015a;Karapandza, 2016;Kim et al, 2017;Liang et al, 2018;?, ? ;Pérez & Tavits, 2017;Roberts et al, 2015;Sutter et al, 2015;Thoma & Tytus, 2018).…”
Section: P R E -P U B L I C a T I O N D R A F Tmentioning
confidence: 92%
“…Such an approach has recently been taken up by a growing number of economists who have sought to test whether cross-linguistic differences in the grammaticization of FTR 1 , affect speakers' future orientation (K. Chen, 2013;S. Chen, Cronqvist, Ni, & Zhang, 2017;Chi, Su, Tang, & Xu, 2018;Fasan, Gotti, Kang, & Liu, 2016;Figlio, Giuliano, Özek, & Sapienza, 2016;Galor, Özak, & Sarid, 2016;Guin, 2017;Hübner & Vannoorenberghe, 2015a;Karapandza, 2016;Kim, Kim, & Zhou, 2017;Liang, Marquis, Renneboog, & Sun, 2018;?, ? ;Mavisakalyan, Tarverdi, & Weber, 2018;Pérez & Tavits, 2017;Roberts, Winters, & Chen, 2015;Sutter, Angerer, Glätzle-rützler, & Lergetporer, 2015;Thoma & Tytus, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been corroborated for a whole range of significant economic outcomes (e.g. Chen, 2013;Guin, 2015;Chen et al, 2017;Mavisakalyan et al, 2018;Godlewski and Weill, 2019;Chi et al, 2020).…”
Section: Introductionmentioning
confidence: 57%
“…Third, and directly relevant to our study, the literature has shown that absence of inflectional future tense affects speakers' inter-temporal preferences (Sutter et al, 2018) and induces more future-oriented behaviours including higher saving (Chen, 2013;Guin, 2015), higher investment in health (Chen, 2013) and education (Galor et al, 2020), higher propensity to become entrepreneurs (Campo et al, 2020), and raised environmental concern and action (Mavisakalyan et al, 2018) at the level of individuals and/or countries. At the corporate level, lack of inflectional future tense is associated with higher precautionary cash holdings (Chen et al, 2017), higher investment in research and development (Chi et al, 2020), and higher loan spreads and higher collateral use in loan contracts (Godlewski and Weill, 2019). We extend this literature by considering a novel outcome: religiosity.…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, I do not put much emphasis on these results and focus on the inflectional marking. Closest to my own research is work done by Chi et al (2020). They find in their work that countries with a weak FTR language and companies from such countries invest more into R&D. My research adds to the existing literature by not assigning companies the characteristic of the official language of the country they are based in but to focus directly on board members and their native language.…”
mentioning
confidence: 84%